Влияние поверхностного натяжения на закономерности всплытия одиночного пузырька и группы пузырьков в промежуточном режиме - Богданов, Сергей Юрьевич (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
In the present work the results of an experimental study of the effect of the surface tension coefficient on the dynamics of the ascent of a single bubble and a group of air bubbles in the range of Reynolds numbers Re=200–700 have been presented. New experimental data on the shape, size and bubbles trajectory in the presence of surfactant molecules at the gas-liquid interface have been obtained. New results on the ascent velocity of a group of bubbles in the presence and absence of a surfactant in liquid have been presented.